Sea level anomaly and earthquake predictions: endangered countries prognostications - Saif Utsha, Abid Ebna; Noman, Mahfuzealahi; Hassan, Raini (Penerbit UTHM, 2019)
Climate change is one of the factors that affect weather and natural disaster. It is extremely difficult to predict a natural disaster. This paper is going to focus on two different types of natural hazard that is going to affect people rising sea level and earthquake. The aim of this paper is to use predictive analysis on both sea level anomaly and earthquake as well as listing down the countries who will face problem in future. The results would be deduced by data analysis. There are several existing machine learning algorithms which are currently used to predict earthquake. In thi analysis, deep learning algorithm will be used to see whether it can predict the occurrence of these events more accurately. The technique used in this paper can be upgraded further in future to help the endangered countries to be prepared better against these sudden calamities.